2012
DOI: 10.1002/prot.24200
|View full text |Cite
|
Sign up to set email alerts
|

Structural features of cholesteryl ester transfer protein: A molecular dynamics simulation study

Abstract: Cholesteryl ester transfer protein (CETP) mediates the net transfer of cholesteryl esters from atheroprotective high-density lipoproteins to atherogenic low-density lipoproteins or very-low-density lipoproteins. Inhibition of CETP raises high-density lipoprotein cholesterol (good cholesterol) levels and reduces low-density lipoprotein cholesterol (bad cholesterol) levels, making it a promising drug target for the prevention and treatment of coronary heart disease. Although the crystal structure of CETP has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 41 publications
(71 reference statements)
10
40
0
Order By: Relevance
“…CETP directionally bound to HDL is consistent with many earlier reports, including i) a CETP-mediated net transfer of CE into VLDL34, ii) CETP bridging HDL and LDL instead of bridging two HDL or LDL particles13, iii) the distal portion of the N-terminal β-barrel domain of CETP being more flexible in solution than is indicated by its crystal structure14; and iv) MD simulations showing that the penetration of the N-terminal β-barrel domain of CETP into the HDL surface generates an opening that allows CE to access the CETP tunnel15. However, our results are inconsistent with those of other investigators who have shown that CETP binds to the edge of discoidal HDL35 via an interaction with apoA-I36, and atomistic and coarse-grained simulations of CETP–HDL interaction which have shown that the N-terminus helix-X domain of CETP penetrates deeply into the HDL particle core37.…”
Section: Discussionsupporting
confidence: 91%
“…CETP directionally bound to HDL is consistent with many earlier reports, including i) a CETP-mediated net transfer of CE into VLDL34, ii) CETP bridging HDL and LDL instead of bridging two HDL or LDL particles13, iii) the distal portion of the N-terminal β-barrel domain of CETP being more flexible in solution than is indicated by its crystal structure14; and iv) MD simulations showing that the penetration of the N-terminal β-barrel domain of CETP into the HDL surface generates an opening that allows CE to access the CETP tunnel15. However, our results are inconsistent with those of other investigators who have shown that CETP binds to the edge of discoidal HDL35 via an interaction with apoA-I36, and atomistic and coarse-grained simulations of CETP–HDL interaction which have shown that the N-terminus helix-X domain of CETP penetrates deeply into the HDL particle core37.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the glycans probably play a part in modulating the CEs transfer through the hydrophobic tunnel of CETP. Flaps Ω1∼Ω6 and Helix‐X of CETP‐N and CETP‐G are indeed flexible, consistent with previous atomistic MD simulations . However, the peak RMSF values of the N‐terminal of CETP‐G are higher than those of CETP‐N, especially for the Ω4 and Ω5 flaps.…”
Section: Resultssupporting
confidence: 88%
“…This variant of MD results could attribute to the simulation time and different initial model. During our simulations, the missed (C1 S2 K3 G4) and mutated residues (C131A N88D N240D N341D) were reversed, and the bound lipids were all removed, while original crystal structure with inhibitor or lipids in previous works . Of note, both flap Ω1 and Ω2 were flexible than other flaps in CETP‐C .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations